2021
DOI: 10.3390/jcm10235678
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Robotic-Assisted Bronchoscopy Platforms in the Sampling of Peripheral Pulmonary Lesions

Abstract: Robotic-assisted bronchoscopy is one of the newest additions to clinicians’ armamentarium for the biopsy of peripheral pulmonary lesions in light of the suboptimal yields and sensitivities of conventional bronchoscopic platforms. In this article, we review the existing literature pertaining to the feasibility as well as sensitivity of available robotic-assisted bronchoscopic platforms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 32 publications
1
11
0
1
Order By: Relevance
“…Initially in human cadavers, the PRECISE‐1 study reported a 100% rate of target localization and 80% of successful nodule puncture, both superior to EMB guidance and ultrathin bronchoscopy, 16 with similar rates reported by Chen et al 15 Recent human studies found comparable successful navigation, ranging from 88% to 98% using either EMB or shape‐sensing technology 24,25 . Reported diagnostic yield for RAB with or without R‐EBUS ranges from 69.1% to 88% 24,26–29 . We achieved a 100% rate of efficacy to reach and sample the target nodule, and an overall diagnostic yield of 87.6% for RAB.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Initially in human cadavers, the PRECISE‐1 study reported a 100% rate of target localization and 80% of successful nodule puncture, both superior to EMB guidance and ultrathin bronchoscopy, 16 with similar rates reported by Chen et al 15 Recent human studies found comparable successful navigation, ranging from 88% to 98% using either EMB or shape‐sensing technology 24,25 . Reported diagnostic yield for RAB with or without R‐EBUS ranges from 69.1% to 88% 24,26–29 . We achieved a 100% rate of efficacy to reach and sample the target nodule, and an overall diagnostic yield of 87.6% for RAB.…”
Section: Discussionsupporting
confidence: 64%
“…24,25 Reported diagnostic yield for RAB with or without R-EBUS ranges from 69.1% to 88%. 24,[26][27][28][29] We achieved a 100% rate of efficacy to reach and sample the target nodule, and an overall diagnostic yield of 87.6% for RAB.…”
Section: Discussionmentioning
confidence: 92%
“…The ARCHIMEDES system has the advantage of additionally providing information regarding the surrounding vessels next to the lesion. Monarch is another platform regarded as a robotic-assisted method that we use under the guidance of computed tomography (11). In the case of a single nodule positive for NSCLC without distant metastasis, we can perform surgery or ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, only two platforms are available (Monarch and ION by Intuitive Surgical), with more to come [ 126 ]. Both devices’ steerable catheters have a small outer diameter, making it feasible for them to reach the peripheral areas of the lung, theoretically improving stability and control over traditional bronchoscopy and increasing diagnostic yield [ 126 ]. However, despite RB reaching deeper into the lung, lesion size still plays a role in diagnostic accuracy.…”
Section: Endoscopic Identification Of a Pplmentioning
confidence: 99%